Optimization of financing for renewable energy expansion projects in Ukraine - Kryshtal, Halyna (Management and Entrepreneurship: Trends of Development, 2025)
The article is dedicated to the analysis of current financial and economic mechanisms supporting renewable energy in Ukraine and identifying the main problems that hinder investment activity in this sector. The purpose of the study is to identify ways to optimize the financing of renewable energy projects and propose solutions to overcome existing barriers. The article discusses the main mechanisms of state support, such as "green" tariffs, auctions for RES projects, tax incentives, and financing through international organizations, as well as identifying problems related to the instability of the legislative framework, high initial costs, and risks for investors.The methodological basis of the study includes the analysis of existing financial and economic mechanisms and international experience in the field of renewable energy. The author uses a comparative analysis of policies of different countries and a practical approach to studying investment attraction mechanisms.The author proposes a number of ways to improve the investment climate, including ensuring legislative stability, developing new financial instruments, expanding state support, and promoting public-private partnership mechanisms. This will reduce financial barriers and mitigate investment risks.The practical view on solving RES issues in Ukraine focuses on the need to establish stable policies, attract international finances, develop new financial instruments, and actively involve the private sector. This will contribute to the development of a sustainable energy sector in the country and ensure energy independence and environmental security in the future.JEL Classification: Q40